2004
DOI: 10.1128/jcm.42.4.1605-1608.2004
|View full text |Cite
|
Sign up to set email alerts
|

Chromatography Paper Strip Method for Collection, Transportation, and Storage of Rotavirus RNA in Stool Samples

Abstract: We developed a novel method that uses sodium dodecyl sulfate-EDTA-treated chromatography paper strips to collect unconcentrated fresh stool samples. After the paper strips were stored for 4 months at room temperature, rotavirus RNA could be successfully amplified by using reverse transcriptase PCR. The use of filter paper strips as a specimen support allows (self-)collection of stool samples by untrained persons. Diarrheal stool samples from remote areas can be stored and transported to a central diagnostic la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 21 publications
1
17
0
Order By: Relevance
“…Previously we showed that pathogenic bacteria such as Vibrio cholerae , enterotoxigenic E. coli , enteropathogenic E. coli , Salmonelle typhimurium and Shigella dysenteriae , were not able to survive on the SDS/EDTA strips [16]. The biosafety test performed in this study demonstrated that adenoviruses also lost infectivity upon contact with the SDS/EDTA strips (Figure 2).…”
Section: Resultsmentioning
confidence: 55%
See 1 more Smart Citation
“…Previously we showed that pathogenic bacteria such as Vibrio cholerae , enterotoxigenic E. coli , enteropathogenic E. coli , Salmonelle typhimurium and Shigella dysenteriae , were not able to survive on the SDS/EDTA strips [16]. The biosafety test performed in this study demonstrated that adenoviruses also lost infectivity upon contact with the SDS/EDTA strips (Figure 2).…”
Section: Resultsmentioning
confidence: 55%
“…Filter paper sampling has been successfully used for screening studies of rotaviruses [16], noroviruses [17], human herpesviruses 6 and 7 [14], human immunodeficiency virus [13,18], hepatitis C virus [19], measles virus [20] and others viruses.…”
Section: Introductionmentioning
confidence: 99%
“…Fecal samples containing RVA were collected and shipped to the Rega Institute for Medical Research using chromatography paper strips as previously described [39].…”
Section: Methodsmentioning
confidence: 99%
“…RV strains DRC88 and DRC86 were collected from patients in the Democratic Republic of Congo in 2003, during an outbreak of acute diarrhea among young children under 5 years of age, at the Kalembe-Lembe Pediatric hospital in Kinshasa, DRC. Fecal samples containing these RV isolates were collected at the Institut National de Recherche Bio-Medicale and were transported to the Rega Institute, University of Leuven, Belgium, using chromatography paper strips (54).…”
Section: Methodsmentioning
confidence: 99%